Circus activities as a health intervention for children, youths, and adolescents: a scoping review protocol. Issue 1 (21st January 2022) - Coulston, Free; Cameron, Kate L.; Spittle, Alicia; Sellick, Kath; Toovey, Rachel
ABSTRACT: Objective: This scoping review aims to map the evidence on circus activities described and/or evaluated as a health intervention for children, youths, and adolescents. Increased understanding of how these interventions work, and gaps identified, will allow researchers and practitioners to advance the science behind these approaches. Introduction: Circus activities are proposed in the literature as a health intervention, due to their variety, non-competitive nature, and potential to develop fundamental physical and social skills. For the purposes of this review, circus activities as a health intervention are defined as aerial, acrobatic, equilibristic, and manipulation skills taught to participants to maintain, improve, or modify health, functioning, or health conditions. Inclusion criteria: English-language evidence will be considered where circus activities as a health intervention are described and/or evaluated for participants up to 24 years of age, or who are defined as children, youths, or adolescents. Literature will be excluded where the focus of the intervention is clowning, magic, or drama games, or where circus activities are not the therapeutic part of the activity. Methods: MEDLINE (Ovid), CINAHL Complete (EBSCO), Scopus (Elsevier), PsycINFO (Ovid), ProQuest Dissertations and Theses Global, and Google Scholar will be searched for peer-reviewed and gray literature. No restriction on dates, type, methodology, or setting will be imposed, but limits will include "human" and "English language." Screening and data extraction will be performed by two independent reviewers. Reference lists of included sources will be screened. Results will be presented in diagrammatic or tabular format, alongside a narrative description, under headings aligning with the research sub-questions.